2013
DOI: 10.1016/j.bone.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged alendronate treatment prevents the decline in serum TGF-β1 levels and reduces cortical bone strength in long-term estrogen deficiency rat model

Abstract: Introduction While the anti-resorptive effects of the bisphosphonates (BPs) are well documented, many questions remain about their mechanisms of action, particularly following long-term use. This study evaluated the effects of alendronate (Ale) treatment on TGF-β1 signaling in mesenchymal stem cells (MSCs) and osteocytes, and the relationship between prolonged alendronate treatment on systemic TGF-β1 levels and bone strength. Methods TGF-β1 expression and signaling were evaluated in MSCs and osteocytic MLO-Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
9
0
3
Order By: Relevance
“…Meanwhile, we showed that knockout of PAR-1 inhibited tumor growth, angiogenesis and osteoclastogenesis both in vitro and in vivo. Previous studies 13,38 have confirmed that osteoclastic destruction could release and activate TGF-b stored in bone matrix, which would further activate PAR-1 in GCTSCs, fueling the cycle (Fig. 6g).…”
Section: Discussionmentioning
confidence: 61%
“…Meanwhile, we showed that knockout of PAR-1 inhibited tumor growth, angiogenesis and osteoclastogenesis both in vitro and in vivo. Previous studies 13,38 have confirmed that osteoclastic destruction could release and activate TGF-b stored in bone matrix, which would further activate PAR-1 in GCTSCs, fueling the cycle (Fig. 6g).…”
Section: Discussionmentioning
confidence: 61%
“…Another important point of this study was the choice of the TGF-β1 marker to accomplish the immunohistochemical evaluation. This marker is responsible for maintaining a constant bone mass, acting directly on the regulation of osteoblast differentiation and promoting polymorphonuclear cell chemotaxis, broblast proliferation, and collagen I synthesis (5). TGF-β1 is a physiological regulator of osteoblast differentiation and a key mediator of the coupling of osteoblast differentiation and osteoclastic bone resorption, which is required for skeletal homeostasis (26).…”
Section: -Discussionmentioning
confidence: 99%
“…Other studies had also proved the relation between them, suggesting that ALN acts directly on this marker, increasing its level (5, 6) A smaller dosage of ALN (1 mg/kg) contributed with less negative impact on the TGF-β1 marker compared to the higher dosage (3 mg/kg), as noted in this study. A study by Jei et al (5) concluded that prolonged reduction of bone turnover after alendronate treatment in female rats increased TGF-β1 production by bone marrow cells and periosteal osteoprogenitors. Table II.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-b has direct effects on the regulation of osteoblast differentiation; its reduction in osteoblasts has been shown to expand bone mineral concentration and bone mass [8][9][10]. VEGF, a known promoter of angiogenesis, stimulates neovascularization and promotes fracture healing, and also regulates activity of osteoclasts and osteoblasts [11,12].…”
Section: Introductionmentioning
confidence: 99%